Pengaruh Media Pembelajaran Flashcard Terhadap Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam Kelas IV SD Al-Madina Wonosobo - Waisatul Kurnia; Robingun Suyud El Syam; Ahmad Zuhdi (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Learning problems in schools are often caused by uninteresting methods and media, which reduce students’ interest and learning outcomes. This study aims to determine the effect of using flashcard learning media on students' learning outcomes in Islamic Religious Education (IRE) for fourth-grade students at SD Al-Madina Wonosobo. The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group. The sample consisted of two classes: the experimental class used flashcards, while the control class applied the lecture method. Data were collected through pretests and posttests and analyzed using t-tests and gain tests. The results showed a significant difference in learning outcomes between the two classes, with higher posttest scores and gain values in the experimental class. The use of flashcards effectively enhanced students' understanding of the material, especially memorization topics such as Asmaul Husna, and created a more engaging and interactive learning atmosphere. The implications of this research suggest that visual learning media such as flashcards can be an effective strategy to improve students' learning achievement and motivation in IRE classes, while also encouraging teachers to be more innovative in applying suitable learning media.